Effectiveness of Slow Stroke Back Massage (SBBM) on blood pressure, anxiety, and depression among older people with hypertension: A quasi-experimental study - Patonengan, Gita Sandy; Mendrofa, Fery Agusman Motuho; Hani, Umi (YCAB Publisher & IAKMI SULTRA, 2023)
Background: The high incidence of hypertension among older adults requires the efforts of healthcare workers to prevent complications that can worsen the condition. Hypertension can also lead to anxiety and depression due to a combination of factors, such as a physiological decline in physical condition. One of the non-pharmacological therapies considered for reducing blood pressure, anxiety, and depression is slow stroke back massage (SSBM). Objectives: The study aimed to examine the effectiveness of SSBM in reducing blood pressure, anxiety, and depression among older adults with hypertension. Methods: This study utilized a quasi-experimental pretest-posttest control group design. The research was conducted in March 2023 with 50 respondents aged 60-74. Aneroid Sphygmomanometer, Geriatric Depression Scale (GDS), and Geriatric Anxiety Scale (GAS) were used for data collection. Mann-Whitney and Wilcoxon tests were used to analyze data. Results: The SSBM therapy in the experimental group was effective compared to the standard therapy in the control group in reducing blood pressure, anxiety, and depression. Conclusion: SSBM therapy is an effective complementary therapy for reducing blood pressure, anxiety, and depression in older adults. Therefore, it can be utilized as a preventive measure against complications that may arise in the older adult population.